2021
DOI: 10.1002/wps.20906
|View full text |Cite
|
Sign up to set email alerts
|

Initial treatment choices to achieve sustained response in major depression: a systematic review and network meta‐analysis

Abstract: Major depression is often a relapsing disorder. It is therefore important to start its treatment with therapies that maximize the chance of not only getting the patients well but also keeping them well. We examined the associations between initial treatments and sustained response by conducting a network meta-analysis of randomized controlled trials (RCTs) in which adult patients with major depression were randomized to acute treatment with a psychotherapy (PSY), a protocolized antidepressant pharmacotherapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…For less severe depression, medication should not be used, but psychotherapy should be offered. This approach is also supported by a recent meta-analysis [ 52 ].…”
Section: Discussionmentioning
confidence: 79%
“…For less severe depression, medication should not be used, but psychotherapy should be offered. This approach is also supported by a recent meta-analysis [ 52 ].…”
Section: Discussionmentioning
confidence: 79%
“…We note here that by clinicians, we primarily refer to general physicians, although note that other healthcare professionals can also be involved in detecting depression and therefore our consideration of “detection” is not limited to medical doctors. Time to diagnosis/treatment: Missed diagnosis is closely linked with delays to both detection and treatment initiation for depression (and in some cases a delay to treatment after detection). After recognition/diagnosis (Step 1), treatments span the whole stepped care pathway (Steps 2–5). Rates of pharmacological/psychological treatment: As the mainstay interventions for MDD, it was considered important to include both pharmacological (antidepressants; Steps 3–5) and psychological therapies (Steps 2–5), which have more or less [2527] equivalent efficacy. Rates and frequency of follow-up contacts after treatment: A key tenet of stepped-care approaches is ensuring continuity of care [28], and thus healthcare contacts are critical for monitoring treatment effects (including efficacy, tolerability, and adherence). …”
Section: Resultsmentioning
confidence: 99%
“…3. Rates of pharmacological/psychological treatment: As the mainstay interventions for MDD, it was considered important to include both pharmacological (antidepressants; Steps 3-5) and psychological therapies (Steps 2-5), which have more or less [25][26][27] equivalent efficacy. 4.…”
Section: Treatment Gap Identificationmentioning
confidence: 99%
“…This large body of research suggests that all psychotherapies have comparable effects, although non-directive counseling may be somewhat less effective than other therapies [2]. This research has shown that the effects of psychotherapies are comparable to those of pharmacotherapy and that combined treatment is more effective than psychotherapy and pharmacotherapy alone [3], while in the longer term, combined treatment and psychotherapies are more effective than pharmacotherapy [4].…”
Section: Introductionmentioning
confidence: 99%